Minority Rights in a Multicultural Society in Indonesia - Zuhud Al Khaer, Muh; Rasyid, Muhammad Firdaus; Hastira, Muh. Fichriyadi; Pratama, Galank (Golden Ratio of Social Science and Education, 2025)
This paper discusses important issues relating to the protection of the rights of minority groups in pluralistic societies, with a particular focus on separatist groups. In the context of diverse societies, minority groups often face significant challenges, ranging from discrimination to violations of their human rights. This article examines these issues with an approach that combines international and national law and analyzes cases that reflect violations of minority rights. From an international law perspective, the protection of minority rights is regulated by various instruments, such as the Convention on Civil and Political Rights and the Declaration of Human Rights. However, its implementation is often hampered by inadequate or contradictory national policies. On the other hand, national laws that do not accommodate minority groups can worsen the situation, especially when it comes to separatist groups that are often seen as a threat to state sovereignty. This article also reviews the steps taken through international mediation and national policy reform to ensure separatist groups receive fair treatment. By reviewing a wide range of literature and case studies, this paper offers a deeper understanding of the importance of an inclusive approach to protecting the rights of minority groups and promoting harmony in pluralistic societies.